DRIVING FACTOR ANALYSIS OF LAND USE CHANGE USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (CASE: DAS WAERUHU OF AMBON CITY) - Aryanto Boreel; Lydia. R. Parera; Meliani Meliani (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
Land development in the Waeruhu watershed moves dynamically due to changes in land cover/land use. The phenomenon of land use change is inseparable from the demand for land along with the increasing population in Ambon City. The aim of this study was to determine the factors that influence changes in land cover/land use in the Waeruhu watershed. Analysis of the factors that influence land use change using the AHP (Analytical Hierarchy Process) method. Factors analyzed in this study include settlements, trade and service centers, educational facilities, roads and rivers. Determination of respondents in this study was determined by purposive sampling, namely Bapedalitbang Ambon City, Maluku River Hall, and Academics. The results showed that settlements had a weighted factor (0.40) which had the most influence on land use changes in the Waeruhu watershed, while the least influential factor was river network with a factor weight of (0.06). Changes in land use that occur in the Waeruhu watershed are thought to be triggered by the increasing rate of population growth which has an impact on increasing the need for land to be built up.